Response of Productivity Traits of Soft Wheat Crop (Sham 10) to Nitrogen Fertilization and Potassium Humate in the Coastal Region in Syria - علوش, غياث; قبيلي, صالح; الحافي, علاء (Latakia University Journal -Biological Sciences Series, 2022)
A filed experiment was conducted using a complete randomized block design at Jableh-Bustan saleh seasons 2018-2019. The aim was to evaluate the effect of increasing application rates of nitrogen fertilizer (N: 0, 100, 200, 300 and 400 kg N/h-1) and humate (H: 0, 2.5, 5, and 10 kg H/h-1) on productivity components and N uptake of bread wheat (triticum aestivum sp. Sham 10). The number grain and weight/spike, weight of thousand grains, grain yield were recorded. N concentration in grain was determined and percent protein and N uptake was calculated. The application of N fertilizer increased significantly productivity parameters (number and weight if grain/spike, and weight of 1000 grain). The increase was gradual with increasing rate of N fertilizer up to N300, beyond which there was no significant increase. The same was true for grain yield which reached 10.66 ton/h-1, and grain protein reached 20.02%. The application of humate or/and nitrogen fertilization led to an increase in number and weight of grain/spike and percent protein when humate was added at a rate of 2.5 kg/h-1 only. These effects were reflected in a gradual increase in grain yield to reach 4.96 to/h-1 in N0H10 treatment compared to 1.58 ton/h-1 in the control treatment (N0H0). The combined effect of applying both N and humate was evident in which the highest grain yield (10.66 ton/h-1) obtained in treatment (N300), and increased to 13.62 ton/h-1 for the same N application rate with 2.5 kg humate/h-1.